Motivators and Deterrents to Diet Change in Low Socio-Economic Pakistani Patients With Cardiovascular Disease. (November 2019) - Barolia, Rubina; Petrucka, Pamela; Higginbottom, Gina Awoko; Khan, Faris Farooq Saeed; Clark, Alexander M.
This study explores factors that affect the people of low socioeconomic status regarding food choices after diagnosis with cardiovascular disease. Qualitative approach was used to identify the important factors associated with dietary changes as a result of their disease. Twenty-four participants were interviewed from two cardiac facilities in Karachi, the largest metropolitan city of Pakistan. Data were analyzed to identify the themes using the interpretative description approach. While most participants understood the need for dietary changes, few were able to follow recommended diets. Their food choices were primarily influenced by financial constraints as well as cultural, familial, and religious values and practices. The challenge for health care providers lies in understanding the economical, sociocultural, and religious factors that influence behavioral changes which, in turn, affect dietary choices. It is apparent that cardiovascular risk and disease outcomes for the people of low socioeconomic status are likely to escalate. Thus, it is necessary to address the sociocultural, religious, and behavioral factors affecting dietary choices. Achieving this imperative requires an intersectorial, multilevel intervention for the prevention of cardiovascular diseases in people of low socioeconomic status.